Volcanogenic mercury and plant mutagenesis during the end-Permian mass extinction: Palaeoecological perturbation in northern Pangaea - Paterson, Niall W; Rossi, Valentina M; Schneebeli-Hermann, Elke (Elsevier, 2024)
The end-Permian extinction (EPE) (251.9 Ma) is considered the most severe biotic crisis in Earth’s history. Rapid climatic change and oceanic acidification triggered by Siberian Traps volcanism culminated in a widely documented mass extinction in the marine realm, but the event’s impact on terrestrial ecosystems, particularly plant communities, is less well understood. While the existence of a floral mass extinction at the Permian-Triassic Boundary (PTB) is still debated, there is mounting evidence for pervasive mutagenesis among various plant lineages, as expressed by the high incidence of aberrant spores and pollen grains. Previous studies have proposed a causal relationship between increased UV-B flux and plant mutagenesis across the PTB, yet the role of volcanically derived heavy metals as a contributing factor has received considerably less attention. Here we present the results of a high-resolution palynological, sedimentological, and geochemical analysis of a continuous and previously unstudied PTB section from the Norwegian Arctic. The study reveals an abrupt increase in the levels of heavy metals across the EPE negative carbon isotope excursion (CIE). Palynological analysis indicates disruption, and a phased transition of plant communities at the PTB, without a significant turnover in species or decrease in diversity. However, the abrupt appearance and elevated abundance of aberrant palynomorphs coincides with increased concentrations of As, Co, Hg, and Ni, which is interpreted as compelling evidence for heavy metal-induced stress and genetic disturbance in plant communities during the EPE. We hypothesise that biomagnification of these elements may have been a significant driver for the end-Permian biotic crisis. Our findings are correlated via biostratigraphy and chemostratigraphy with other circum-Arctic PTB sections described in the literature, demonstrating the isochroneity and facies independence of these widespread palaeoecological changes. Keywords: Permian-Triassic boundary,Teratology, ...